DESIGN EDUCATION OPPORTUNITIES FOR PERSONAL DEVELOPMENT IN LIEPAJA UNIVERSITY (LATVIAN) - Klasone, Inta (European Scientific Journal, ESJ, 2014)
The 21st century raises a number of problems to be resolved in education. One of the problems is the contradictory nature of global and individual phenomena. Globalization without losing the sense of belonging to one‘s living space, through implementing one‘s potential according to the well-kept traditions, active participation in one‘s own society life and its growth is also an important role of Design Education. Designers are the ones that can have a significant impact and can model the human living space, artistically designing and constructing the spatial environment and its elements as well as items of everyday use. The changing nature is influenced by public taste, technological progress, and reflection of national trends in design. This marks the need to study the Design Education opportunities. Educational research nowadays engages pedagogues, psychologists, philosophers, sociologists, persons who are interested in development of higher education in Latvian as a whole. In order to implement the best Design Education, it is important to understand the nature of personality and its development characteristics. Studying the development of human personality scholars take into account the individual needs and interests, choices and motivation for actions, self-esteem. Design education of Liepaja University is in close conjunction with its Research Activity Strategy for 2010 - 2016 and Development Strategy for 2008 - 2018 laying out that scientific research and creative activity at Liepaja University is a fundamental prerequisite for sustainable development. As well, that Liepaja University is open to international cooperation which promotes science and research based learning, development of the knowledge society and implementation of research results in the economy.